A Practical Guide to Sequencing Genomes and Transcriptomes - Sanchez-Flores, Alejandro; Abreu-Goodger, Cei (Current Topics in Medicinal Chemistry, 2014)
The emergence of new DNA sequencing technologies has allowed an exponential growth of genomic and transcriptomic data that ultimately yielded important results to several areas such as medicine and biology. This continuous technological progress presents several advantages and caveats that have to be considered for each new method. In this review, we describe the so-called second and third generation DNA sequencing technologies, how they changed the study of genomes and transcriptomes, and most importantly, what are the key factors that should be considered in a sequencing project. Taken together, we present a “sequencing project map” that includes a practical and graphical cost-benefit analysis for genome and transcriptome projects which allows scientist to easily classify their workflow into one of our proposed templates according to the goals and experimental design of the project at hand. In all, this review reflects the pros and cons of the most widely adopted experimental designs, sequencing technologies, and exposes them to help scientists interested in these tools to choose the best strategy for their project.
Keywords: transcriptomics